Quality factor investigation by using trapezoidal subwavelength grating waveguide micro-ring resonator based on graphene - Akbari, Elnaz; Mosallanezhad, Gholamreza; Ariannejad, Mohammad Mahdi; Yupapin, Preecha Promphan; Afroozeh, Abdolkarim (Elsevier, 2018)
Sub-wavelength grating waveguide-based micro-ring resonators (SWGMRs) are interesting areas of photonics and optoelectronics application. The nature of high bending loss has constrained the SWGRM to achieve a small radius with the satisfied quality factor. In this work, we have demonstrated that the bend loss in SWG waveguide has been substantially reduced by using optimized trapezoidal silicon pillars as compared to rectangular silicon pillars (conventional SWG). The Q factor variation has been increased 70.8% via the optimized trapezoidal silicon pillars. The simulation is conducted using miniaturized Si micro-ring resonators with the radius less than 5 μm and achieved Q > 104 with single-mode operation over the entire large free-spectral range. Moreover, the graphene has been used to coat upon the proposed design, which showed a further enhancement in Q-factor.